The Effect of Development in Respiratory Sensory Gating Measured by Electrocortical Activations - Pei-Ying S. Chan; Chia-Hsiung Cheng; Andreas von Leupoldt (Neural Plasticity)
The perception of respiratory sensations can be of significant importance to individuals for survival and greatly impact quality of life. Respiratory sensory gating, similar to somatosensory gating with exteroceptive stimuli, is indicative of brain cortices filtering out repetitive respiratory stimuli and has been investigated in adults with and without diseases. Respiratory gating can be tested with the respiratory-related evoked potential (RREP) method in the electroencephalogram with a paired inspiratory occlusion paradigm. Here, the RREP N1 component elicited by the second stimulus (S2) shows reduced amplitudes compared to the RREP N1 component elicited by the first stimulus (S1). However, little is known regarding the effect of development on respiratory sensory gating. The present study examined respiratory sensory gating in 22 typically developed school-aged children and 22 healthy adults. Paired inspiratory occlusions of 150-ms each with an inter-stimulus-interval of 500-ms were delivered randomly every 2–4 breaths during recording. The main results showed a significantly larger RREP N1 S2/S1 ratio in the children group than in the adult group. In addition, children compared to adults demonstrated significantly smaller N1 peak amplitudes in response to S1. Our results suggest that school-aged children, compared to adults, display reduced respiratory sensory gating.